INVESTIGATING THE IMPACT OF CULTURE AND RELIGION ON MIGRANT ENTREPRENEURIAL INTENTION: A VALIDATING RESEARCH - Vandor, P; Franke, N. (Journal of Allied Research in Management and Entrepreneurship (JARME), 2022)
Entrepreneurial intention is a crucial factor in the success of entrepreneurship, and understanding the motivating factors for migrants seeking better economic conditions and positions in their new country is fundamental. This study aims to examine the impact of religion on migrant entrepreneurs’ decision-making and intention. The researchers collected primary data through surveys that were sent to migrants across different continents. The results showed that religion has a significant influence on entrepreneurial intention among migrants. The study found that religion was a fundamental consideration for migrants when deciding on entrepreneurial intention or choice. It further revealed that culture shock is a prevalent experience among migrant entrepreneurs and business owners when they move to a new location. The research contributes to the understanding of the effects of religion on entrepreneurial intention and how it affects migrants in their new or current location. Policymakers should recognize the role of religion in entrepreneurship and design policies to support migrant entrepreneurs.